2008
DOI: 10.1021/es800262k
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling in Daphnia magna, Part II: Validation of a Copper Specific Gene Expression Signature with Effluent from Two Copper Mines in California

Abstract: Genomic technologies show great potential for classifying disease states and toxicological impacts from exposure to chemicals into functional categories. In environmental monitoring, the ability to classify field samples and predict the pollutants present in these samples could contribute to monitoring efforts and the diagnosis of contaminated sites. Using gene expression analysis, we challenged our custom Daphnia magna cDNA microarray to determine the presence of a specific metal toxicant in blinded field sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 17 publications
(33 reference statements)
3
47
0
Order By: Relevance
“…Copper concentrations used in this study, though high, are not uncommon in Californian surface waters [39], especially the lowest concentration investigated. Results from this study are indicative of short-term exposure responses.…”
Section: Discussionmentioning
confidence: 79%
“…Copper concentrations used in this study, though high, are not uncommon in Californian surface waters [39], especially the lowest concentration investigated. Results from this study are indicative of short-term exposure responses.…”
Section: Discussionmentioning
confidence: 79%
“…As a demonstrative exercise using the results of our one-year time series analysis (Tables 2 and 3), we would ascribe a NOTEL for RDX at <0.83 mg/L. However, in contrast to Poynton et al [41] and Lobenhofer et al [43] who utilized a dose series and a single timepoint for assessing the NOTEL, our experimental design included the investigation of differential expression through a time series. This time-series element provided an additional element of scrutiny in assessing functional impacts resulting from changes in gene expression.…”
Section: Implications Of One-year Time Series Results To Notelmentioning
confidence: 99%
“…Recently, NOTEL has been proposed as a means of incorporating transcriptomics or gene expression results into a risk assessment framework [41][42][43]. The studies that developed methods to assess NOTEL [41,43] each emphasize the importance of discerning true differentially expressed transcripts from false positives resulting from type II statistical error.…”
Section: Implications Of One-year Time Series Results To Notelmentioning
confidence: 99%
See 1 more Smart Citation
“…Helbing et al (2007a,b) compared effects of two forms of thyroid hormone and three chemicals that affect thyroid function, methimazole, propylthiouracil, and perchlorate, to identify specific genes and gene expression profiles that could serve as indicators of exposure to thyroidactive chemicals. In a series of non-EDC-related studies, Poynton et al identified distinct gene expression profiles for Daphnia magna exposed to three metals, Cu, Cd, Zn (Poynton et al, 2007), and later demonstrated that blinded field samples collected from copper mining sites clustered with the laboratory-derived Cu-specific expression profile (Poynton et al, 2008). Although limited to profiles for three metals, this was one of the first studies to demonstrate that gene expression analysis could predict environmental exposure to a specific pollutant (Poynton et al, 2008).…”
Section: Transcriptional Fingerprints and Biomarkersmentioning
confidence: 99%